Menilik Demokrasi Pendidikan Ki Hajar Dewantara dalam Kelas Kontemporer - Ardiansyah, Zidane; Hendriwanto, Hendriwanto (Balai Diklat Keagamaan Bandung, 2024)
This study aims to explore how teacher interpret and implement Ki Hajar Dewantara's educational democracy in contemporary classrooms. The research employs a qualitative method with a single case study design, where data were collected through open-ended interviews and observations of a teacher applying democratic principles in their classroom. The data were processed using thematic analysis with descriptive coding. The findings reveal four main themes: (1) Democratic Values in Education through Ki Hajar Dewantara’s Philosophy, (2) Educational Democracy within the Framework of the Trilogi Kepemimpinan, (3) Innovation in Democratic Education, and (4) The Challenges of Democracy in Contemporary Classrooms. The results show that the teacher interprets Dewantara’s democratic principles as responsible freedom for students to express their opinions and equal rights regardless of background. This is implemented through the Leadership Trilogy, positioning the teacher as a role model, replacing punishment with class agreements, and fostering a positive classroom environment. The teacher also applies democratic principles by incorporating local approaches, experiential learning, and integrating spiritual aspects to counter neoliberalism and neoconservatism in education. The challenges faced by the teacher in implementing educational democracy relate to the ever-changing kodrat alam and kodrat zaman of students, as well as differing views among the Tripusat Pendidikan. However, these challenges are addressed through reflection and self-improvement.